Economic & Cultural Distance & Regional Integration: Evidence from Gravity Model Using Disaggregated Data for Pakistan (The Pakistan Development Review, 2020)
This study applies generalised gravity models to analyse Pakistan’s bilateral trade flows at commodity level using both panel as well as cross-sectional data estimation techniques. The empirical findings indicate that distance and size of the economy are the major determinants of commodity trade flows. For many commodities, real exchange rate, trade preferences, being landlocked, technological differences and market size are vital factors, which boost bilateral trade flows. Remarkably, there is an inverse relationship between bilateral trade flows and a common border. As far as regional trading blocs are concerned, the results show that ASEAN is a potentially significant destination for Pakistan’s commodity trade. The findings illustrate that in the case of SAARC trading partners, the potential of trade has not materialised. For the purpose of robustness of our results, we have also used agricultural and non-agriculture related trade costs. Estimates indicate that trade costs between Pakistan and its trading partners are highly significant and negatively related to commodity trade flows, while other empirical findings confirm the robustness of the results. Keywords: Gravity Model, Commodity, Regional Integration, ASEAN, ECO, OIC, SAA